2019
DOI: 10.1158/0008-5472.can-19-1112
|View full text |Cite
|
Sign up to set email alerts
|

Drugging MYCN Oncogenic Signaling through the MYCN-PA2G4 Binding Interface

Abstract: MYCN is a major driver for the childhood cancer, neuroblastoma, however, there are no inhibitors of this target. Enhanced MYCN protein stability is a key component of MYCN oncogenesis and is maintained by multiple feedforward expression loops involving MYCN transactivation target genes. Here, we reveal the oncogenic role of a novel MYCN target and binding protein, proliferationassociated 2AG4 (PA2G4). Chromatin immunoprecipitation studies demonstrated that MYCN occupies the PA2G4 gene promoter, stimulating tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…Our studies suggested that an alternate region of PA2G4-p48 might be a potential protein-protein interaction site, specifically interacting with the oncoprotein, MYCN (44).…”
Section: Lxxll Motif and Pa2g4-p42/ Pag4-p48-isoform Conserved Proteimentioning
confidence: 71%
See 4 more Smart Citations
“…Our studies suggested that an alternate region of PA2G4-p48 might be a potential protein-protein interaction site, specifically interacting with the oncoprotein, MYCN (44).…”
Section: Lxxll Motif and Pa2g4-p42/ Pag4-p48-isoform Conserved Proteimentioning
confidence: 71%
“…In our study, we used structurebased drug design methods to target a binding site boarded by helix α2 (aa S44-K62) (44). We hypothesized that the known PA2G4 inhibitor WS6 (54) bound to the same groove on PA2G4 that MYCN binds to, a groove boarded by helix α2 (44). Further biological assessment of WS6 confirmed that it had an inhibitory effect on PA2G4-p48's oncogenic role in malignant neuroblastoma cells in vitro and in vivo (44).…”
Section: Functional and Structural Differences Between The Pa2g4-p42 mentioning
confidence: 93%
See 3 more Smart Citations